ANALYSIS OF THE APPLICATION OF DIGITAL MARKETING COMMUNICATION STRATEGIES IN INCREASING CAR SALES BY PT. HADJI KALLA TOYOTA MALILI BRANCH - Andi Winda Fatimah Wali Samad; Hafied Cangara; Arianto Arianto (Jurnal Scientia, 2023)
Writer do study this at PT. Hadji Kalla Malili Branch. Objective study This is For know strengths, weaknesses, opportunities as well as threat of the promotional strategy implemented kukan company and also for know appropriate alternative promotion strategy used by companies, in matter This is PT. Hadji Kalla Malili Branch. Method research used in study This that is study qualitative. Data used are primary data and secondary data. Primary data obtained from party competent company give description. Researcher gather information in a manner direct with do interview deep. Secondary data obtained direct in already form So like document contains sales data, then from studies References with learn related articles, books and theses with study this. In describe results study used a number of marketing strategy analysis with analyze internal and external factors of the promotional strategy undertaken with give description general about strengths, weaknesses, opportunities as well as threat of the promotional strategy undertaken company. Based on results study using the analysis that combines strengths, weaknesses, opportunities and threats of the promotion strategy company.